2021
DOI: 10.1155/2021/6650413
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of One‐Step Block Method for Solving Second‐Order Fuzzy Initial Value Problems

Abstract: In this article, we present a one-step hybrid block method for approximating the solutions of second-order fuzzy initial value problems. We prove the stability and convergence results of the method and present several examples to illustrate the efficiency and accuracy of the proposed method. The numerical results are compared with the existing ones in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…x−axis shows the value of the approximation solution, y−axis show the value of α-level values, Y, Y are the lower and upper bounds of the exact solution respectively, y, y are the lower and upper bounds of the approximate solution respectively, E = Y − y computes the absolute error of the lower bound approximation, E = Y − y computes the absolute error of the upper bound approximation, h is the step size, TSBM: Two-step Block Method with Third and Fourth Derivatives, EBHDEF: Extended Block Hybrid Backward Differentiation Formula [16], BDF: Block Differentiation Formula [15], BBDF: Block Backward Differentiation Formula [15], OOMB: Optimization of One-Step Block Method [17], RK5: Runge Kutta Method Order Five [14], OHAM: Optimal Homotopy Asymptotic Method [7], FDM: Finite Difference Method [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…x−axis shows the value of the approximation solution, y−axis show the value of α-level values, Y, Y are the lower and upper bounds of the exact solution respectively, y, y are the lower and upper bounds of the approximate solution respectively, E = Y − y computes the absolute error of the lower bound approximation, E = Y − y computes the absolute error of the upper bound approximation, h is the step size, TSBM: Two-step Block Method with Third and Fourth Derivatives, EBHDEF: Extended Block Hybrid Backward Differentiation Formula [16], BDF: Block Differentiation Formula [15], BBDF: Block Backward Differentiation Formula [15], OOMB: Optimization of One-Step Block Method [17], RK5: Runge Kutta Method Order Five [14], OHAM: Optimal Homotopy Asymptotic Method [7], FDM: Finite Difference Method [30].…”
Section: Resultsmentioning
confidence: 99%
“…The biggest drawback of these approaches is the reduction of the second-order FODEs to the system of first-order FODEs, which leads to computational burden and also impacts solution accuracy. To bypass the rigor of reduction, block methods were introduced for the direct solution of second-order FODEs in [15][16][17]. However, due to the order of the block methods developed by these studies, it is observed that there is still room to improve the accuracy of their obtained results in terms of absolute error.…”
Section: Introductionmentioning
confidence: 99%
“…gr (x, β, α z ) ∂x4 = z gr (x, β, α z ), (5.20)z gr (0) = z gr (0) = z gr (0) = z gr (0) = z (4) gr (0) = −1 + β + 2(1 − β)α 0 ,(5.21)whereβ, α z = α 0 ∈ [0, 1]. The solution of IVP (5.20)-(5.21) is z gr (x, β, α 0 ) = e x [−1 + β + 2(1 − β)α 0 ] .…”
mentioning
confidence: 99%